Alcohol Abuse Associated With Increased Risk of Angiographic Vasospasm and Delayed Cerebral Ischemia in Patients With Aneurysmal Subarachnoid Hemorrhage Requiring Mechanical Ventilation - Zhao, Lei; Cheng, Chao; Peng, Liwei; Zuo, Wei; Xiong, Dong; Zhang, Lei; Mao, Zilong; Zhang, Jin'an; Wu, Xia; Jiang, Xue; Wang, Peng; Li, Weixin (Frontiers in Cardiovascular Medicine, 2022)
Objective Although alcohol abuse has been indicated to cause cerebral aneurysm development and rupture, there are limited data investigating the impact of alcohol abuse on outcomes after aneurysmal subarachnoid hemorrhage (aSAH). This study aims to investigate whether alcohol abuse increases the risk of angiographic vasospasm and delayed cerebral ischemia (DCI) in critically ill patients with aSAH. Methods We conducted a secondary analysis based on a retrospective study in a French university hospital intensive care unit. Patients with aSAH requiring mechanical ventilation hospitalized between 2010 and 2015 were included. Patients were segregated according to alcohol abuse (yes or no). Multivariable logistic regression analysis was used to identify the independent risk factors associated with angiographic vasospasm and DCI. Results The patient proportion of alcohol abuse was dramatically greater in male than that in female (p<0.001). The SAPSII score on admission did not show statistical difference. Neither did WFNS and Fisher scores. Patients with alcohol abuse were more likely to develop angiographic vasospasm (OR 3.65, 95% CI 1.17-11.39; p = 0.0260) and DCI (OR 3.53, 95% CI 1.13-10.97; p = 0.0294) as evidenced by multivariable logistic regression analysis. Conclusions In this study, patients with alcohol abuse are at higher odds of angiographic vasospasm and DCI, which are related to poor prognosis following aSAH. These findings are important for prevention and clinical management of aSAH.